Understanding the joint impacts of soil architecture and microbial dynamics on soil functions: insights derived from microscale models - Pot, Valérie; Portell, Xavier; Otten, Wilfred; Garnier, Patricia; Monga, Olivier; Baveye, Philippe C. (Wiley, 2022)
Over the last decades, a new generation of microscale models has been developed to simulate soil microbial activity. An earlier article (Pot et al., 2021) presented a detailed review of the description of soil architecture and microbial dynamics in these models. In the present article, we summarise the main results obtained by these models according to six model outputs: growth and spatial organisation of microbial colonies, soil hydraulic conductivity, coexistence and trophic interactions of microorganisms, temporal dynamics of the amount of solid and dissolved organic matter in soil and, microbial production of CO2. For each of these outputs, we draw particular attention to the respective roles of soil architecture and microbial dynamics, and we report how microscale models allow for disentangling and quantifying them. We finally discuss limitations and future directions of microscale models in combination with the on-going development of high-performance imaging tools revealing the spatial heterogeneity of the actors of soil microbial activity.
Keywords: bacteria models; fungi models; spatial accessibility; ecological interactions; soil organic matter